001. Large Wilms Tumor in A 3-Year-Old Child at Abdoel Wahab Sjahranie Hospital: A Case Report - Muladi, Jafar Sidiq; Soenjoto, Dadik Agus (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p001, 2024)
Background : Wilms tumor (WT) is the most common primary renal tumor in children, typically diagnosed between ages of 1 and 5, with peak incidence at 3 years. Imaging modalities like ultrasound, CT, and MRI can predict WT in up to 95% of cases, but histological subtypes necessitate tissue examination. Management usually involves surgery, chemotherapy, and sometimes radiation therapy. This report aims to present and analyze the clinical presentation, diagnostic approach, and management of an unusually large Wilms tumor in a 3-year-old child at our hospital, highlighting the challenges and treatment strategies for such rare case. Case: A 3-year-old girl with hematuria for two weeks and an abdominal mass that had been present for years but had enlarged in the last 2-3 months. Physical examination revealed a palpable mass in the left hypochondrium. Abdominal CT showed grade II/III left hydronephrosis with a cystic and solid lesion measuring 10.3 x 8.1 cm and enlarged right para-aortic glands. Conclusion: This case underscores the importance of a multidisciplinary approach involving surgery and chemotherapy to effectively manage WT and highlights the positive prognosis associated with timely treatment